Musculoskeletal Wide-Detector CT Kinematic Evaluation: From Motion to Image - Teixeira, Pedro A. Gondim; Gervaise, Alban; Louis, Matthias; Raymond, Ariane; Formery, Anne-Sophie; Lecocq, Sophie; Blum, Alain (Seminars in Musculoskeletal Radiology, 2015)
Kinematic computed tomography (CT) allows identification of fine positional anomalies of bones during motion and under stress and has a potential role in the evaluation of dynamic joint diseases. The increasing width of CT detector systems has made kinematic CT clinically available. Information on acquisition protocol, patient preparation, and the influence of motion on image quality is scarce in the literature despite the obvious importance for the clinical application of this technique. In this article we review the current knowledge on the relation between motion and artifacts, recommendations for the acquisition protocol, as well as current indications for kinematic CT.
Keywords: computed tomography; kinematic; 4D; joints; protocol recommendations; patient training